Altered mental status predicts mortality in cardiogenic shock – results from the CardShock study. Issue 1 (February 2018) - Kataja, Anu; Tarvasmäki, Tuukka; Lassus, Johan; Køber, Lars; Sionis, Alessandro; Spinar, Jindrich; Parissis, John; Carubelli, Valentina; Cardoso, Jose; Banaszewski, Marek; Marino, Rossella; Nieminen, Markku S; et al.
Background: Altered mental status is among the signs of hypoperfusion in cardiogenic shock, the most severe form of acute heart failure. The aim of this study was to investigate the prevalence of altered mental status, to identify factors associating with it, and to assess the prognostic significance of altered mental status in cardiogenic shock. Methods: Mental status was assessed at presentation of shock in 215 adult cardiogenic shock patients in a multinational, prospective, observational study. Clinical picture, biochemical variables, and short-term mortality were compared between patients presenting with altered and normal mental status. Results: Altered mental status was detected in 147 (68%) patients, whereas 68 (32%) patients had normal mental status. Patients with altered mental status were older (68 vs . 64 years, p =0.04) and more likely to have an acute coronary syndrome than those with normal mental status (85% vs . 74%, p =0.04). Altered mental status was associated with lower systolic blood pressure (76 vs . 80 mmHg, p =0.03) and lower arterial pH (7.27 vs . 7.35, p <0.001) as well as higher levels of blood lactate (3.4 vs . 2.3 mmol/l, p <0.001) and blood glucose (11.4 vs . 9.0 mmol/l, p =0.01). Low arterial pH (adjusted odds ratio 1.6 (1.1–2.2), p =0.02) was the only factor independently associated with altered mental status. Ninety-day mortality was significantly higher (51% vs . 22%, p <0.001) among patients with altered mental status. Conclusions: Altered mental status is a common clinical sign of systemic hypoperfusion in cardiogenic shock and is associated with poor outcome. It is also associated with several biochemical findings that reflect inadequate tissue perfusion, of which low arterial pH is independently associated with altered mental status.